PROFESSIONAL EXPERIENCE: REMEDIAL CLASSES IN SEVENTH GRADE BASED ON PROBLEM SOLVING - Jiménez Sánchez, Dilan Josué (2026)
In this essay, a professional experience is presented in which the knowledge acquired in the Mathematics Education program at the University of Costa Rica (UCR) was applied. Specifically, the theoretical frameworks on problem-solving proposed by Polya and Schoenfeld were implemented in the planning and development of remedial classes for a seventh-grade course within the Costa Rican educational system.